Community’s perception of measles immunization in Sleman - Yulia Irene Wahyunarni; Riris Andono Ahmad; Atik Tri Ratnawati (Berita Kedokteran Masyarakat (BKM), 2016)
Community perception of measles immunization in SlemanPurposeThis study conducted to explore the community’s perception of measles immunization in Sleman.MethodsA phenomenological study was conducted involving interviews of the head of neighborhood’s ladies who were highly respected by their citizens, mothers with toddlers but refused immunizations, immunized toddler mothers, health workers who did not immunize their children based on information from FGDs of mothers who refused immunization, a toddler father who does not allow his child to be immunized, community leaders and religious leaders, in the village of Sukoharjo whose area has been infected with measles outbreaks. ResultsThe study found that first, people perceived that immunization has no benefit and even causes side effects for children’s under-five health. Second, the community perceives that immunization of measles is not mandatory because of the lack of the government's role in enforcing regulations related to measles immunization. Third, the perception of people against measles immunization is influenced by the behavior of health workers and religious leaders. ConclusionsThe side effects of measles immunization, the influence of health workers' behavior and religious figures related to non-immunization against measles, and the lack of government's role in enforcing regulations related to the appeal of measles immunization are the factors that influence community's perception and a decision of not doing measles immunization. Government appeals related to immunization need to be improved, and in addition, education related to measles hazard should be done to the community, religious leaders and health workers to increase awareness and awareness of the dangers of measles.